2018
DOI: 10.1002/adma.201704876
|View full text |Cite
|
Sign up to set email alerts
|

Citrate Improves Collagen Mineralization via Interface Wetting: A Physicochemical Understanding of Biomineralization Control

Abstract: Biological hard tissues such as bones always contain extremely high levels of citrate, which is believed to play an important role in bone formation as well as in osteoporosis treatments. However, its mechanism on biomineralization is not elucidated. Here, it is found that the adsorbed citrate molecules on collagen fibrils can significantly reduce the interfacial energy between the biological matrix and the amorphous calcium phosphate precursor to enhance their wetting effect at the early biomineralization sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
142
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(157 citation statements)
references
References 55 publications
6
142
0
Order By: Relevance
“…Recently, the important structural role of citrate in regulating bone hydroxylapatite-like (HA) minerals has been uncovered: citrate molecules are not only studded on the surface of apatite nanocrystals [116] and bridged between the apatite mineral platelets, stabilizing bone apatite [117, 118], but also control the size and crystallinity of HA particles [119]. In addition to citrate-HA interactions, citrate-collagen (the primary bone organic matrix) interactions promote collagen biomineralization by improving the wetting effect at the collagen-mineral interface to directly regulate the mineralization process [120]. All the above studies demonstrate that citrate is a strongly bound and integral part of native bone, serving as a key mineralization regulator.…”
Section: Biology Considerations For Biomaterials Design and Applicationmentioning
confidence: 99%
“…Recently, the important structural role of citrate in regulating bone hydroxylapatite-like (HA) minerals has been uncovered: citrate molecules are not only studded on the surface of apatite nanocrystals [116] and bridged between the apatite mineral platelets, stabilizing bone apatite [117, 118], but also control the size and crystallinity of HA particles [119]. In addition to citrate-HA interactions, citrate-collagen (the primary bone organic matrix) interactions promote collagen biomineralization by improving the wetting effect at the collagen-mineral interface to directly regulate the mineralization process [120]. All the above studies demonstrate that citrate is a strongly bound and integral part of native bone, serving as a key mineralization regulator.…”
Section: Biology Considerations For Biomaterials Design and Applicationmentioning
confidence: 99%
“…Along with pAsp, it is likely that citrate and inorganic ions, such as Mg 2+ and PO 4 3− , contributed to the crystal structures seen in the current study. It has been proposed that citrate penetrates collagen fibrils where it then provides additional nucleation sites for intrafibrillar calcium‐phosphate crystal growth (Shao et al, ). Additionally, when adsorbed on collagen fibrils, citrate has been reported to improve wetting between collagen and the mineral precursor phase (Shao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that citrate penetrates collagen fibrils where it then provides additional nucleation sites for intrafibrillar calcium‐phosphate crystal growth (Shao et al, ). Additionally, when adsorbed on collagen fibrils, citrate has been reported to improve wetting between collagen and the mineral precursor phase (Shao et al, ). These effects appear to promote intrafibrillar mineralization, even in the absence of pAsp (Delgado‐López et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The main aim of this work was not the study of basic mechanisms of collagen mineralization and the effect of citrate in this process, which was already reported [17,18], but the preparation for the first time of a new luminescent bioinspired composite Col/Ap material. Therefore the luminescent properties properties of the as-synthesised samples were fully investigated.…”
Section: Luminescent Properties Of Eu 3+ -Doped Mineralized Collagen mentioning
confidence: 99%
“…Recently, Hu et al [13] using nuclear magnetic resonance ( 13 C-NMR) have revealed that citrate accounts for about 5.5 wt % of total organic matrix of bone and it is strongly bound to the surface of the apatite nanoparticles (1 molecule/2 nm 2 ). Its presence and abundance should not be considered adventitious but would reflect an important role in the biomineralization process [13,14]; therefore, the study of the effect of citrate in the formation of biomimetic apatite nanoplatelets as well as in collagen mineralization has become a subject of intense research in the last years [15][16][17][18][19]. The last results have shown that the use of citrate is an interesting and straightforward nature inspired strategy to control the chemical-physical features of the apatite for the development of improved nanoparticle-based biomaterials [20][21][22].…”
Section: Introductionmentioning
confidence: 99%